Health literacy of Breast Cancer and Its Related Factors in Kashanian Women: Breast cancer health literacy - Batooli, Zahra; Mohamadloo, Azam (Advances in Nursing & Midwifery, 2022)
Abstract Introduction: Health literacy is related to better adherence to the recommendations of health care providers, health care appointments and acceptance of preventive care such as cancer screening. Considering the importance and role of health literacy in breast cancer screening, this study was conducted to investigate health literacy about breast cancer and its related factors among women. Methods: An analytic cross-sectional study was conducted on 186 women who were referring to health care centers in Kashan city in Iran in 2020 with basic literacy. All the participants filled out a questionnaire developed based on Health literacy of breast cancer and its related factors using the questionnaires of AHL-C (Assessment of Health Literacy in Cancer Screening) and Breast-CLAT. The random cluster sampling method was applied to select participants. The statistical analysis was performed with chi-square in SPSS 18. Results: The majority of the participants were 40-49 and marital. The total of health literacy in half of the participants was medium. The most undesirable and desirable dimensions of health literacy were related to numerical literacy and reading literacy, respectively. Determinants related to health literacy were identified as the following: education, visit a doctor due to having a problem in the breast and cancer family history. Moreover results showed that a significant correlation between comprehensive literacy and prior knowledge dimension with performing BSE. Conclusions: Of all the health literacy dimensions examined, Prior knowledge and comprehensive literacy were the strongest predictors with do breast self-examination. It can be concluded that, promoting health literacy could be effective for the primary prevention of non-communicable diseases and early diagnosis. We recommend educating all women for the prevention and early diagnosis of breast cancer.